Prediksi Jumlah Penjualan Rumah di Bojongsoang ditengah Pandemi Covid-19 dengan Metode ARIMA - Kurniawan, Alit Fajar; Pane, Syafrial Fachri; Awangga, Rolly Maulana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
This study aims to determine the accuracy of the ARIMA method with the Carmer matrix in forecasting or predicting the number of house sales in the Bojongsoang area which is still experiencing a period of crisis. The data used in this study is secondary data in the form of time series data on the number of house sales. In the ARIMA method, we perform stationary data, then look for autoregressive (AR), moving average (MA), and ARMA (Autoregressive and Moving Average) values. From the available data, the number of house sales has decreased, therefore forecasting is carried out using the ARIMA (1,1,1) model for future home sales to assist property developers in estimating future development projects. the results of the forecasting carried out using the ARIMA (1,1,1) method, which shows that the prediction of the number of house sales in the Bojongsoang area in the June - December period experienced a stable number of house sales